2023
DOI: 10.1038/s41467-023-35927-0
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis lowers the genetic barrier to SARS-CoV-2 neutralizing antibody escape

Abstract: Waves of SARS-CoV-2 infection have resulted from the emergence of viral variants with neutralizing antibody resistance mutations. Simultaneously, repeated antigen exposure has generated affinity matured B cells, producing broadly neutralizing receptor binding domain (RBD)-specific antibodies with activity against emergent variants. To determine how SARS-CoV-2 might escape these antibodies, we subjected chimeric viruses encoding spike proteins from ancestral, BA.1 or BA.2 variants to selection by 40 broadly neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 40 publications
2
25
1
Order By: Relevance
“…2A and 2B, middle and bottom ). The broadening of the escape pathways in pre-Omicron-elicited antibody responses with Omicron VOCs compared to WH-1 has been observed in other studies (46, 65) and could provide additional flexibility for escape.…”
Section: Resultssupporting
confidence: 55%
“…2A and 2B, middle and bottom ). The broadening of the escape pathways in pre-Omicron-elicited antibody responses with Omicron VOCs compared to WH-1 has been observed in other studies (46, 65) and could provide additional flexibility for escape.…”
Section: Resultssupporting
confidence: 55%
“…Epistatic interactions between mutations add substantial complexity of their adaptive landscapes are believed to play an important role in the virus evolution. The proposed in our study a network-based model for the analysis of non-additive contributions of the RBD residues indicated that some convergent Omicron mutations such as G446S (BA.2.75, BA.2.75.2, XBB), F486V (BA.4, BA.5, BQ.1, BQ.1.1), F486S, F490S (XBB.1), F486P (XBB.1.5) can display epistatic relationships with the major stability and binding affinity hotspots which may allow for the observed broad antibody resistance induced by these mutations [68]. Using atomistic simulations, the ensemble-based mutational scanning of binding/stability and network-based approaches, we showed that the binding affinity hotspots R498 and Y501 serve as central mediators of the interfacial communities in the RBD-ACE2 complexes.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic mapping of the epistatic interactions between the 15 BA.1 RBD mutations relative to the Wu-Hu-1 strain showed evidence of compensatory epistasis in which immune escape BA.1 mutations can individually reduce ACE2 binding but are compensated through epistatic couplings with affinity-enhancing mutations including Q498R and N501Y [67]. Recent evolutionary and functional studies revealed strong epistasis between pre-existing substitutions in BA.1/BA.2 variants and antibody resistance mutations acquired during selection experiments, suggesting that epistasis can lower the genetic barrier for antibody escape [68].…”
Section: Introductionmentioning
confidence: 99%
“…The latest variant B.1.1.529 (Omicron) and its newer sub-lineages (BA.2, BA.4, BA.5, BQ.1, and XBB.1) have acquired resistance to vaccine-induced immunity and has been infecting large population worldwide (11)(12)(13)(14)(15). It is highly plausible that there is still much more genetic space that SARS-CoV-2 can explore to navigate through host immunity without compromising transmissibility (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%